An Automatic Calibration Method for Near-infrared Camera in Optical Surgical Navigation - RongQian Yang; Xuan Si; QinYong Lin; Ken Cai (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
Optical surgical navigation system (SNS) with near-infrared tracking system is becoming extensively used in clinics, and the accuracy of SNS is influenced by the calibration of near-infrared cameras (NIRCs). We propose an automatic calibration method for NIRCs. The method is based on a designed calibration board. In our experiments, corners are automatically extracted to obtain the parameters of NIRCs. This method has the advantages of saving time, efficiency in computation, high accuracy, and reliability. In our experiments, an NIRC can be calibrated in only 5 s. Meanwhile, the average relative errors of the focal length and principal point are 0.87% and 1.39%, respectively.